Frailty, malnutrition, healthcare utilization, and mortality in patients with dementia and cognitive impairment obtained from hospital administrative data - Merchant, Reshma Aziz; Dong, Ying Qiu; Kumari, Shikha; Murphy, Diarmuid (Frontiers in Medicine, 2025)
IntroductionWith aging populations, the prevalence of dementia, frailty and malnutrition will increase. The aim of this study is twofold (a) to determine the demographic data, including frailty and malnutrition prevalence in older patients with diagnosis of dementia and/or cognitive impairment and (b) to determine its impact on outcomes such as length of stay (LOS), readmission and mortality stratified by frailty status.MethodsRetrospective single-center cohort study conducted using hospital database on older patients ≥65 yrs. admitted to a tertiary hospital between March 2022 and Dec 2023 and discharged with either primary or secondary diagnosis of dementia or cognitive impairment. Data on age, gender, ethnicity, comorbidities, discharge diagnoses, Hospital Frailty Risk Score (HFRS), Clinical Frailty Scale (CFS), activity of daily living (ADL), 3-Minute Nutrition Screening and outcomes such as LOS, readmission, mortality and cost of hospitalization were extracted. Those aged between 65 to 74 years old were categorized as “young-old,” and ≥75 years old as “old-old.”ResultsDementia or cognitive impairment diagnosis was prevalent in 8.6% (3090) older patients, and 33.7% were malnourished. 54.5% were female with a mean age of 82.0 years. Almost one fourth were dependent on ADL. Based on frailty defined by (i) HFRS—26.0% had intermediate and 18.2% high frailty (ii) CFS—41.0% were mild/moderately frail, and 32.2% severely frail. Median LOS was 8 days. 30 and 90-days readmission rates were 23.2 and 35.4%, respectively. In-hospital mortality was 7.8% and 30-day mortality 14.0%. High HFRS (aOR 1.511, 95% CI: 1.089–2.097; p = 0.013), severe frailty (aOR 4.325, 95% CI: 0.960–2.684; p < 0.001) and terminal frailty (aOR 39.762, 95% CI: 18.311–86.344; p < 0.001) were significantly associated with inpatient mortality. Intermediate HFRS (aOR 1.682, 95% CI: 1.380–2.050; p < 0.001), mild/moderate frailty (1.609, 95% CI: 1.254–2.065; p < 0.01), high HFRS (aOR 2.178, 95% CI: 1.756–2.702; p < 0.001) and severe frailty (2.333, 95% CI: 1.804–3.017; p < 0.01) were significantly associated with 30-days readmission. The impact of malnutrition on healthcare utilization was highest in the old-old with high HFRS and severe frailty.ConclusionFrailty and malnutrition have significant impact on healthcare utilization, readmission rates, and mortality among older adults with dementia and/or cognitive impairment.